ANALYSIS OF NONLINEAR CUMULATIVE DAMAGE MODEL CONSIDERING STRENGTH DEGRADATION - LI Wei (Jixie qiangdu)
Fatigue damage accumulation and strength degradation occur simultaneously and interact with each other during service of engineering structures. In order to establish an improved Corten-Dolan cumulative damage model that takes the effects of strength degradation in consideration,strength degradation coefficient was deduced by analyzed the strength degradation model,then the exponential parameter d in the Corten-Dolan model was defined as an exponential function related to the strength degradation coefficient. Effectiveness of the improved Corten-Dolan model was verified by fatigue test data of material and comparison with other references. The results show that the improved Corten-Dolan model predicts fatigue life accurately,prediction is more accurate than the traditional Corten-Dolan model.